2020
DOI: 10.1007/s42773-020-00063-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochar amendments and its impact on soil biota for sustainable agriculture

Abstract: Beneficial microbes in soil biota are known to enhance plant growth by stimulating the nutrient supply and by devising certain mechanisms to cope up with the biotic (diseases) or abiotic (salinity, drought, and pollution) stresses. Owing to their effectiveness and sustainability concerns, the application of microbes in the agricultural sector has seen a positive surge recently. Biochar has been commended as an exemplary carrier material for beneficial microbes in the soil ecosystem. Biochar is generally produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 124 publications
2
21
0
Order By: Relevance
“…Soil organic carbon (SOC) was an important carbon resource for saprotrophic fungi ( Bardgett, 2005 ) and was significantly positively correlated to soil salinity ( Supplementary Figure 4 ). The increment of SOC implies higher soil porosity and water retention capacity ( Pathy et al, 2020 ), providing shelters for soil fungi. Meanwhile, the impacts of geographic distance and soil depth on fungal community dissimilarity imply the stochastic process and dispersal limitation of soil fungi ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic carbon (SOC) was an important carbon resource for saprotrophic fungi ( Bardgett, 2005 ) and was significantly positively correlated to soil salinity ( Supplementary Figure 4 ). The increment of SOC implies higher soil porosity and water retention capacity ( Pathy et al, 2020 ), providing shelters for soil fungi. Meanwhile, the impacts of geographic distance and soil depth on fungal community dissimilarity imply the stochastic process and dispersal limitation of soil fungi ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the biochar amendment could reduce the proportion of cell wall-bound Cd in roots, which caused easier Cd translocation from the cortex to the stele in the root and up to the aboveground parts (Li et al 2019b). Biochar increased soil porosity and provided more habitat for microorganisms (Pathy et al 2020). This measure may also stimulate the associated soil microorganisms, thus facilitating the transport of Cd and Zn from the plant to the aboveground.…”
Section: Effect Of Bbc and Flooding On Phytoremediation Capacity Of S...mentioning
confidence: 98%
“…The application of oxidants is generally thought to inhibit the microbial activity. Although PS might inhibit the microbial activity, PS can also be activated by soil components, such as soil minerals and organic matters, and generate free radicals for abiotic degradation of contaminants (Pathy et al 2020). Furthermore, the addition of nZVI in PS slightly enhanced the removal of contaminants.…”
Section: Kinetics Of Pollutant Degradation In Soilmentioning
confidence: 99%